(untitled) (Research, Society and Development, 2023)
Football is essential to prepare a child or adolescent to have a healthy physical life and considerable motor development is observed that accelerates maturation due to significant exposure to the demands it requires. Therefore, working on these skills brings improvements to the child’s development in sport. Therefore, this research aims to present the benefits of strength training in children who play football and futsal. The present study is a literature review, carried out through a systematic and exploratory approach with the following theme: Effects of strength training on children in football and futsal. After reading the abstract and applying the inclusion and exclusion criteria, 14 articles remained. The final sample of the number of materials after reading the text in full and applying the exclusion criteria, totaled 07 articles. Our results suggest that power and strength training improve the skills of children who play soccer and futsal. Power, strength and plyometric training, in addition to being safe, is a great option for improving the skills of children who play football and futsal. However, there is a clear need for more research and studies on physical and strength training in football and futsal, given that it is a globally recognized practice, it is necessary to cover other means such as in-depth exercises such as sprints, jumps and agility in soccer.